2017
DOI: 10.1007/s11695-017-2784-5
|View full text |Cite
|
Sign up to set email alerts
|

The Inequity of Bariatric Surgery: Publicly Insured Patients Undergo Lower Rates of Bariatric Surgery with Worse Outcomes

Abstract: Publicly insured patients are significantly less likely to undergo bariatric surgery. As a group, these patients experience higher rates of obesity and related complications and thus are most in need of bariatric surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 37 publications
3
20
0
Order By: Relevance
“…In countries where healthcare is mostly provided by public systems, such as Canada, the United Kingdom, Spain, Australia, and Brazil, constraints in access to surgery for obesity and metabolic disorders result from the high demand compared with limited availability of specialized services. Consequently, many centers have years-long waiting lists with hundreds or thousands of patients [4][5][6][7][8]. To deal with this problem, several countries have adopted obesity severity classification systems to identify not only individuals for whom surgical treatment would be most beneficial but also to ascertain individuals with extreme disease severity for whom the surgical risk would be greater than its benefits [9][10][11][12].…”
mentioning
confidence: 99%
“…In countries where healthcare is mostly provided by public systems, such as Canada, the United Kingdom, Spain, Australia, and Brazil, constraints in access to surgery for obesity and metabolic disorders result from the high demand compared with limited availability of specialized services. Consequently, many centers have years-long waiting lists with hundreds or thousands of patients [4][5][6][7][8]. To deal with this problem, several countries have adopted obesity severity classification systems to identify not only individuals for whom surgical treatment would be most beneficial but also to ascertain individuals with extreme disease severity for whom the surgical risk would be greater than its benefits [9][10][11][12].…”
mentioning
confidence: 99%
“…14 Hennings et al found that delays and insurance rejection among the publicly insured seeking bariatric procedures lead to a threefold increase in mortality. 17 The NIH eligibility criteria 29 only allows class II obesity to receive surgery if they have a related comorbidity. Therefore, disease burden bears influence on which patients receive LRYGB at this lower BMI.…”
Section: Discussionmentioning
confidence: 99%
“…Of the nearly 90 thousand in-patient bariatric surgical procedures that were performed in 2006, 75% were white, 55% were above median income, and 82% had private insurance. 3 Additionally Hennings et al 13 found in a case control analysis of the National Inpatient Sample from 2003 through 2010, the population with public insurance has a higher rate of obesity and obesity-related complications but is significantly less likely to undergo bariatric surgery than the privately insured population.…”
Section: Discussionmentioning
confidence: 99%